HLA-B*14 allele predicts HIV-1 mother-to-child-transmission, in Salvador, Brazil - Angulo,Juan Manuel Cubillos (2019)
ABSTRACT Background: Class I human leukocyte antigens, especially the molecules encoded at the B locus (HLA-B), are associated with AIDS progression risk. Different groups of HLA-B alleles have been associated to a protective effect or increasing susceptibility to HIV infection and are expressed from the earliest stages of gestation. Objective: The aim of this study was to evaluate which variants of HLA-B are associated with the risk of HIV vertical transmission in infected pregnant women and in their offspring, in a referral center in Salvador Bahia. Methods: We performed HLA-B genotyping in 52 HIV-infected mothers and their children exposed to HIV-1 during pregnancy (N = 65) in Salvador, Brazil. We compared the HLA-B alleles frequency in mothers, uninfected and infected children, according to the use of antiretroviral prophylaxis. Results: Absence of antiretroviral antenatal and postnatal prophylaxis was significantly associated with vertical transmission of HIV-1 (p = <0.01, and p = <0.01 respectively). Frequency of HLA-B*14 (29.2%, p = 0.002), HLA-B*18 (16.7%, p = 0.04) or HLA-B*14:1 (20.8%, p = 0.01) alleles subgroups were significantly higher in HIV-1 infected children and persisted (HLA-B*14, p = 0.04) even after adjusting for use of antiretroviral prophylaxis. No significant difference in expression of HLA-B alleles was observed among mothers who transmitted the virus compared to those who did not. Conclusions: Expression of HLA-B*14 allele in children exposed to HIV-1 is predictive of vertical transmission and reinforces the important role of genetics in mother-to-child transmission.